The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.3390/w8100437
|View full text |Cite
|
Sign up to set email alerts
|

Re-Linking Governance of Energy with Livelihoods and Irrigation in Uttarakhand, India

Abstract: Abstract:Hydropower is often termed "green energy" and proffered as an alternative to polluting coal-generated electricity for burgeoning cities and energy-insecure rural areas. India is the third largest coal producer in the world; it is projected to be the largest coal consumer by 2050. In the Himalayan state of Uttarakhand, India, over 450 hydroelectric power schemes are proposed or are under development. Hydropower projects ranging from micro hydro (run-of-the-river systems with generating capacity up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…However, a detailed study of the impacts of three run-of-the-river hydroelectric projects in the Indian state of Uttarkhand on the Bhilangana tributary to the Ganges River demonstrated that these schemes also have significant, even devastating, local social and environmental impacts. But the study also identified strategies to use hydropower projects to safeguard, and possibly enhance, the livelihoods of women, youth and men and maintain critical ecosystem services (Buechler et al 2016).…”
Section: Hydroelectric-water-food Nexus In the Ganges Headwatersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a detailed study of the impacts of three run-of-the-river hydroelectric projects in the Indian state of Uttarkhand on the Bhilangana tributary to the Ganges River demonstrated that these schemes also have significant, even devastating, local social and environmental impacts. But the study also identified strategies to use hydropower projects to safeguard, and possibly enhance, the livelihoods of women, youth and men and maintain critical ecosystem services (Buechler et al 2016).…”
Section: Hydroelectric-water-food Nexus In the Ganges Headwatersmentioning
confidence: 99%
“…The study concludes by advocating participatory governance and establishing clear legally enforceable guidelines and mechanisms for benefit sharing, pointing to the example of Nepal, which does mandate sharing benefits with the local communities (Box 1; Buechler et al 2016;WLE 2017b).…”
Section: Hydroelectric-water-food Nexus In the Ganges Headwatersmentioning
confidence: 99%
“…Sustainable water governance comprehends the justice of policies and actions and their impacts on all stakeholders [27]. In "Re-Linking Governance of Energy with Livelihoods and Irrigation in Uttarakhand, India", Buechler et al investigated the impacts of hydropower projects on rural communities in order to derive recommendations to improve the social justice of energy development governance [28]. They conclude that governance instruments can be employed to compensate rural losses and share the benefits of hydropower projects more equitably.…”
Section: Perspectives On Water Management and Governancementioning
confidence: 99%
“…The notion of benefit sharing has evolved from that of compensation to a situation in which local people directly and substantially benefit from infrastructure projects. A benefits-sharing partnership enables the local population to have ownership over the project and to strive for more socially just project outcomes for villagers (Buechler et al 2016). Involving local communities in the decision making on, and development of, appropriate compensation packages can help ensure that the needs of smallholder farmers are taken into account.…”
Section: Involvement Of Local Communitiesmentioning
confidence: 99%